MANAJEMEN MUTU PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF HADITS - Wandra Arasdi; Ilyas Husti; Nurhadi Nurhadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to determine the quality management of Islamic Religious Education from a hadith perspective using a qualitative descriptive research method with a thematic approach, namely by collecting hadiths related to the quality management of Islamic Religious Education. The results of the research show that the term quality management in Arabic is often referred to as ihsan, ihsan is good deeds that are quality, good and beautiful. Thus, ihsan is a benchmark in describing quality management in Islamic Religious Education subjects. The way to realize ihsan from a hadith perspective is that all components involved in the educational process must do the following things: firstly improve the Islamic Religious Education learning process, secondly carry out the learning process optimally, thirdly the learning process must be carried out in a focused manner, fourthly all those involved in the provision of education do not look at age or age, all five of those involved in the provision of education are people who have good competence. These five things can be used as references in improving the quality of Islamic Religious Education.